Solve for X: 3(X + 1) = −2(X − 1) + 6.


Question: Solve for x: 3(x + 1) = −2(x - 1) + 6.

The standard form of a linear equation in one variable is of the form ax + b = 0

Answer: The solution of 3(x + 1) = −2(x - 1) + 6 is x = 1.

Let's solve the given linear equation: 3(x + 1) = −2(x - 1) + 6

Explanation:

Given that

3x + 3 = -2x + 2 + 6

3x + 2x = 2 + 6 - 3   ------> shifting the variables to LHS and constants to RHS

5x = 8 - 3

5x = 5

x = 5/5

x = 1 

Thus, x = 1 is the solution of the given equation.